Failure of rapid diagnostic tests in Plasmodium falciparum malaria cases among travelers to the UK and Ireland: Identification and characterisation of the parasites. (July 2021) - Nolder, Debbie; Stewart, Lindsay; Tucker, Julie; Ibrahim, Amy; Gray, Adam; Corrah, Tumena; Gallagher, Carmel; John, Laurence; O'Brien, Edel; Aggarwal, Dinesh; Benavente, Ernest Diez; van Schalkwyk, Donelly; et al.
Highlights: Malaria cases in UK and Ireland travellers can give false-negative HRP-RDT results. Histidine-rich protein (HRP2/3) deletions can cause false-negative HRP-RDT results. High parasitemia may give false-negative RDT results due to a prozone-like effect. False-negative RDT results may also be a result of low parasite density. Next-generation sequencing can elaborate the breakpoints of HRP2/3 deletions. Abstract: Objectives: Our objective was to systematically investigate false-negative histidine-rich protein 2 rapid diagnostic tests (HRP2-RDT) in imported Plasmodium falciparum malaria cases from travelers to the UK and the Republic of Ireland (RoI). Methods: Five imported malaria cases in travellers returning to the UK and RoI from East Africa were reported to the PHE Malaria Reference Laboratory as negative according to histidine-rich protein (HRP2)-RDT. The cases were systematically investigated using microscopic, RDT, molecular, genomic, and in in vitro approaches. Results: In each case, HRP2-RDT was negative, whereas microscopy confirmed the presence of P. falciparum . Further analysis revealed that the genes encoding HRP2 and HRP3 were deleted in three of the five cases. Whole-genome sequencing in one of these isolates confirmed deletions in P. falciparum chromosomes 8 and 13. Our study produced evidence that the fourth case, which had high parasitemia at clinical presentation, was a rare example of antigen saturation ('prozone-like effect'), leading to a false negative in the HRP2-RDT, while the fifth case was due to low parasitemia. Conclusions: False-negative HRP2-RDT results with P. falciparum are concerning. Our findings emphasise the necessity of supporting the interpretation of RDT results with microscopy, in conjunction with clinical observations, and sets out a systematic approach to identifying parasites carrying pfhrp2 and pfhrp3 deletions.